2021
DOI: 10.7196/samj.2021.v111i12.16262
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-initiated antiretroviral therapy (PIMART)

Abstract: Pharmacist-initiated management of antiretroviral therapy (PIMART)To the Editor: We the undersigned, a collective of pharmacy researchers, practitioners and academics, call on the Minister to consider the following points in response to the input made by the South African Medical Association (SAMA) in relation to pharmacistinitiated management of antiretroviral therapy (PIMART), dated 9 September 2021. We wish to highlight the expertise of pharmacists in all matters relating to the design, production and use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…This finding is consistent with other studies in sub-Saharan Africa, which have shown that pharmacies are perceived as more convenient, more private and less stigmatizing than clinics, particularly by men [73][74][75]. Thus, our study supports the important role of community pharmacies in differentiated HIV care delivery for men in South Africa [76,77] and in sub-Saharan Africa more broadly [75,78,79].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies in sub-Saharan Africa, which have shown that pharmacies are perceived as more convenient, more private and less stigmatizing than clinics, particularly by men [73][74][75]. Thus, our study supports the important role of community pharmacies in differentiated HIV care delivery for men in South Africa [76,77] and in sub-Saharan Africa more broadly [75,78,79].…”
Section: Discussionsupporting
confidence: 92%
“…One mechanism used in the United States is a collaborative practice agreement, which enables pharmacy providers to initiate, adjust and discontinue specified prescription drugs under the remote supervision of a clinician [ 54 ]. Alternatively, formalized training curriculums could be developed to certify interested pharmacy providers in PrEP delivery, like the Pharmacy Initiated Management of Antiretroviral Treatment course in South Africa [ 21 , 55 ]. New public–private partnership frameworks should also be considered to support the delivery of donated public antiretroviral medications [ 56 ] in private settings.…”
Section: Discussionmentioning
confidence: 99%
“…To reach populations that do not commonly seek health services in the public sector, Kenya's National AIDS & STI Control Program (NASCOP) called for evidence on the effectiveness and safety of PrEP delivery at private pharmacies. In collaboration with Kenyan stakeholders, a model of pharmacy‐delivered PrEP services was developed to implement for research purposes [ 10 , 20 ]—one of the first of its kind in Africa [ 21 ]. This model was adapted from a model ongoing in the United States (Seattle, Washington) [ 22 ]; details of the design process are published elsewhere [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that it is feasible to use pharmacies to dispense ART and other chronic medication (62)(63)(64), with a study in Nigeria finding a higher ART continuity rate and viral load suppression in people who utilized pharmacies for refills compared to healthcare facilities (62). There has also been a proposal in South Africa for Pharmacy Initiated ART (PIMART), which will also include PrEP initiations (65). Previous studies the United States of America (United States) and Sub-Saharan Africa also found that actual and potential clients where in support of pharmacy PrEP distribution (66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%